Dependency, privilege, and counter-insurgency: a case study of the industrial elite of Hebron in the occupied West Bank - Arafeh, N (2021)
A central but understudied aspect of the period following the Oslo peace process in 1993 is the rise of a native Palestinian business elite, which have been playing an important role in the political, economic, and social spheres in the West Bank. This thesis focuses on an important group within the indigenous elite—the industrial elite in Hebron, a governorate that has been under-researched despite constituting the industrial and commercial hub of the West Bank. Informed by a political economy approach, this dissertation critically examines how Hebron’s industrial elite accumulated and concentrated their capital, within a larger context of occupation, de-industrialisation, and absence of a sovereign state.